Imagination of the general: the Belarusian language and the Belarusian content of Alexander Yelsky’s works - Koshman, Pavel R. (Journal of the Belarusian State University. Philology, 2025)
The article is devoted to the process of formation and expression of the ideas of the Belarusian community in the national literary tradition. Based on the material of A. Yelsky’s works, the role of the Belarusian language in consolidating the creative forces of Belarus and their search for a common value basis with the Belarusian people are indicated. In the artistic situations of the author’s Belarusian-language communication with the reader, the continuity of tasks for the representation of the Belarusian peculiarity and the construction of the Belarusian identity is traced. The personal creative contribution of A. Yelsky to filling the literature of the late 19th and early 20th centuries with the idea of the historical subjectivity of the Belarusian people is revealed.
Keywords: Alexander Yelsky; Belarusian literature of the 19th century; Belarusian language; Motherland; Belarusian community; identity